Proteolysis Targeting Chimeras (PROTACs) Based on Imatinib Induced Degradation of BCR‐ABL in K562 Cells. Issue 15 (14th April 2023) - Li, Chuang; Zhang, Peng; Chang, Gaojie; Pan, Mingyue; Lu, Fengke; Huang, Jiahao; Wang, Yanzhi; Zhao, Qingyan; Sun, Bingxia; Cui, Yuting; Sang, Feng
Abstract: The proteolysis targeting chimera (PROTAC) technology is widely explored in cancer research and utilized in the treatment of various tumors and malignancies. In the design and optimization of PROTAC, linker is not only critical to the degradation activity of PROTACs, but also greatly affects the membrane permeability, metabolic stability and drug availability. In this study, fifteen new PROTACs based on Imatinib were designed, synthesized, and assessed for their anticancer activity against K562 cells. The CCK‐8 assay results showed that a new PROTAC with a 2‐oxoethyl linker (PROTAC 1 ) exhibited significant antiproliferative activity against K562 (IC50 =0.62±0.02 μM) cells. Western blot analysis showed that PROTAC 1 regulated the protein levels of BCR‐ABL in a dose‐dependent manner and induced degradation of BCR‐ABL in a ubiquitin‐proteasome‐dependent manner in K562 cells. This study provides further evidence for the importance of linker selection in PROTAC design. Abstract : Fifteen new proteolysis targeting chimeras (PROTACs) based on Imatinib and Thalidomide have been designed, synthesized, and evaluated for their antiproliferative activity against K562 cells. PROTAC with a 2‐oxoethyl linker exhibited significant activity against K562 cells (IC50 =0.62±0.02 μM). Western blot results showed that the new PROTAC reduced the level of BCR‐ABL through ubiquitin‐proteasome system (UPS) pathway.